Pola Persebaran Spasial Pelanggan dan Intensitas Pemasaran Ulang Garam CV TMSB di Sumatera Barat - Siti Nurfani; Endah Purwaningsih (Lembaga Yasin AlSys, 2026)
CV Garam Tani Makmur Sejahtera Bersama (TMSB) markets salt products through three sales outlets serving various areas across West Sumatra Province. However, the company lacks spatial information on customer distribution, the reach of resale marketing, and regional market potential as a basis for marketing decision-making. This study aims to analyze the spatial distribution patterns of customers, the reach and intensity of salt resale marketing, and their relationship with regional market potential. The study employed a quantitative descriptive method with a spatial analysis approach. Data were obtained through observation, interviews, documentation, and customer location and resale marketing data and were subsequently analyzed using Average Nearest Neighbor (ANN), Point Distance, Kernel Density Estimation (KDE), and overlay analysis with ArcGIS 10.8. The results showed that 484 customers formed a clustered distribution pattern, with a Nearest Neighbor Ratio of 0.232779, while 51.86% of customers were located within a radius of 0–10 km from the sales outlets. The highest resale marketing intensity was concentrated in Padang City, while Agam Regency and West Pasaman Regency had high market potential but relatively low distribution intensity. These findings indicate that distance and market potential play a role in shaping customer distribution patterns and determining the reach and intensity of CV TMSB’s salt resale marketing in West Sumatra Province. This study provides a practical contribution in the form of spatial information that the company can use to evaluate marketing areas, optimize distribution, and develop market expansion strategies in high-potential areas.